Teaching the Pragmatic Functions of Discourse Markers in Legal Language - Matei, Mădălina (Transilvania University Press, 2020)
Discourse markers are endowed with a prominent textual function as they ensure discursive coherence and cohesion as well as with an interpersonal function that guides the receptors of the legal spoken or written text towards the correct interpretation of the message. This paper illustrates, by relying on a qualitative analysis of discourse markers in Legal English, several manners of efficiently teaching the pragmatic and functional roles of discourse markers in legal English texts to Law students who study English as a foreign language in general and ESP in particular. The main aim is to develop the students’ ability to detect, define, analyze and use discourse markers in written and spoken legal language.
Keywords: discourse markers; functional roles; professional communication; Legal English.